Pengaruh Tagline dan Jingle Iklan Terhadap Pembentukan Brand Awareness - Ismiyadi, Ana; Fanani, Abdul Fatah; Handayani, Sri; Novelia, Diela; Astutik, Wahyu (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2022)
This study aims to analyze "The Influence of Taglines and Jingels on the Formation of Brand Awareness" (Studies on Oreo Ads with the Taglines "Diputar, Dijilat, Dicelupin" and Jingle "Bayangkan Ku Beri Oreo" on Television to students at Institut Pembangunan Airlangga  Surabaya (IPAS)). This study uses a quantitative method, the data source is obtained from primary data sources using a questionnaire as a research instrument. The sample in this study were 37 people. The analytical tools used include validity and reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, F tests, t tests, correlation coefficient tests and coefficients of determination test. The results of statistical analysis explain that: (1) Tagline and Jingle variables together have an effect on Brand Awareness. (2) Tagline variable has no significant effect on Brand Awareness. (3) The Jingle variable has a significant effect on Brand Awareness.